ANALISA FAKTOR TINGKAT KEBERHASILAN DIGITAL MARKETING MELALUI MEDIA SOSIAL FACEBOOK PADA UMKM DI CEPOGO BOYOLALI - Marwati, Fithri Setya; Samrotun, Yuli Chomsatu; Nur Rois, Dimas Ilham; Hamidah, Raisa Aribatul; Susanto, Ryan (JURNAL ILMIAH EDUNOMIKA, 2024)
Social media was originally created for friendships only. However, as time goes by, many people don't want to waste the opportunity to sell. Moreover, all sales activities on social media are almost free. Even if there are additional costs, only for the production of goods. That's why Facebook launched Facebook Marketplace. The purpose of this research is (1) to find out what variables influence a person's level of success in carrying out digital marketing using Facebook, 2) knowing the most dominant and weakest variables that influence a person's level of success in doing digital marketing using Facebook, and (3) knowing the correlation between factors that can influence a person's level of success in doing digital marketing using Facebook. This research empirically analyzes the factors that influence people to do digital marketing using Facebook. The research location was carried out in Cepogo Boyolali. The results of this research conclude that sellers always look at shares and likes, because these are important variables to see buyers' interest. Sellers are also obliged to do this because it indicates that the seller is someone who is always active towards buyers. Sellers must always share experiences using the advertised products. In communication, frequent use of online chat facilities (P10) is the lowest factor; and 2 factors were formed that were able to explain the factors a person does marketing via Facebook. .Factor 1 consists of P1, p2, p3, p4, p5, p7, p10 and p13. Meanwhile, factor 2 consists of variables P6, p8, p9, p11, p12, and p14. Keywords : Digital marketing, Facebook, Success factors